2019
DOI: 10.21203/rs.2.13748/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expansion of sweet taste receptor genes in grass carp (Ctenopharyngodon idellus) coincided with vegetarian adaptation

Abstract: Background: Taste is fundamental to diet selection in vertebrates. Genetic basis of sweet taste receptor in the shaping of food habits has been extensively studied in mammals and birds, but scarcely studied in fishes. Grass carp is an excellent model for studying vegetarian adaptation, as it exhibits food habit transition from carnivory to herbivory. Results: We identified six sweet taste receptors (gcT1R2A-F) in grass carp. The four gcT1R2s (gcT1R2C-F) have been suggested to be evolved from and paralogous to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In support of fish T1R2 adaptive functions, it was recently shown that a subset of four recently duplicated T1R2 paralogs in the herbivorous grass carp displayed enhanced T1R2s / T1R3 responses to plant-specific fructose. The authors suggest that T1R2 gene expansion in this species (possibly deriving from the extra lineage-specific genome duplication of cyprinids [ 64 ]) underlies taste adaptive strategies to dietary transition from carnivore to herbivore food habits [ 19 ]. Similarly, heterologous transfections of T1R2a / b / c / R3 dimeric complexes and testing with a broad range of L-AAs and natural and artificial sugars as potential ligands in the omnivorous zebrafish and medaka fish suggested that duplicated T1R2s in these species may have evolved for tuning a wide range of sensory modalities with a prominent sensitivity to amino acids [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of fish T1R2 adaptive functions, it was recently shown that a subset of four recently duplicated T1R2 paralogs in the herbivorous grass carp displayed enhanced T1R2s / T1R3 responses to plant-specific fructose. The authors suggest that T1R2 gene expansion in this species (possibly deriving from the extra lineage-specific genome duplication of cyprinids [ 64 ]) underlies taste adaptive strategies to dietary transition from carnivore to herbivore food habits [ 19 ]. Similarly, heterologous transfections of T1R2a / b / c / R3 dimeric complexes and testing with a broad range of L-AAs and natural and artificial sugars as potential ligands in the omnivorous zebrafish and medaka fish suggested that duplicated T1R2s in these species may have evolved for tuning a wide range of sensory modalities with a prominent sensitivity to amino acids [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the existence of unique T1R1 and T1R3 genes seems to be a constant feature of vertebrate genomes, numerous T1R2 paralogs have been thus far identified in several fish species [ 4 , 16 , 17 , 18 , 19 ]. Studies on fish taste function using heterologous expression systems revealed that putative sweet T1R2 genes respond to L-amino acids (L-AAs) rather than sugars in omnivore species such as zebrafish ( Danio rerio ) and medaka ( Oryzias latipes ) [ 20 ], or preferentially to plant-specific fructose in the herbivorous grass carp ( Ctenopharyngodon idellus ) [ 19 ]. These observations indicate that T1R2 gene expansion may have served a key role in the evolution of species-specific taste adaptation to diverse habitats and diets.…”
Section: Introductionmentioning
confidence: 99%
“…The study aimed to characterize the distribution of taste receptors in the buccal cavity (tongue, palace, pharynx and lips), and also in tissues known to express taste receptors in mammals [29] and fishes (gill filament, liver, intestine and stomach) [30]. Secondly, we deciphered the modulation of taste receptors in the tongue (presence of taste bud cells) of RT related to different diets.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to mammalian T1Rs, fish T1R3 is mostly co-expressed with either fish T1R1 or T1R2, although cells solely expressing T1R2 have also been reported [4,11]. Moreover, previous studies on functional characterization using heterologous expression systems have demonstrated that fish T1Rs function as heterodimers of T1R1/T1R3 or T1R2/T1R3, similar to mammalian T1Rs, and that these receptors respond to diverse L-amino acids [4,16], although T1R2/T1R3 of herbivorous fish uniquely responds to sugars [17]. Recently, the crystal structure of the extracellular ligand-binding domains of T1R2a, a T1R2 subtype, and the T1R3 heterodimer from medaka fish was reported, which provided a detailed structural insight into the broad amino acid recognition by the receptor [16].…”
mentioning
confidence: 99%